Remembering Aizu : the testament of Shiba Gorō - Shiba, Gorō, 1860?-1945 (University of Hawai'i Press, 1999)
The Meiji Restoration of 1868 is most often seen as a glorious event marking the overthrow of Tokugawa feudalism and the beginning of Japan's modern transformation. Yet it had its dark side. The Aizu domain in northeastern Japan had staunchly supported the old regime. For this it was attacked by the new government's forces from Choshu and Satsuma in the autumn of 1868. Its castle town was burned to the ground, and during a month-long siege, whole families perished. After defeat, the domain was abolished and its samurai population exiled to barren terrain in the far north. Shiba Goro was born into an Aizu samurai family in 1859. He was just ten years old at the time of the attack, which claimed most of his family. In the cruel world of exile, he lived with his father on the edge of starvation, struggling to survive. Eventually making his way to Tokyo, he became a servant, and though born in an enemy domain, gained entrance to a military school of the new regime. Shiba's abilities were recognized, and he rose through the officer ranks to become a full general - a singular distinction for an Aizu samurai in an army dominated by former samurai of the Choshu domain. Remembering Aizu tells of Shiba's earlier years. It is an extraordinary story that provides insights and material for a social history of the Restoration and its aftermath. But above all, it is a vividly rendered personal account of courage and determination, loss and remembrance.